2021
DOI: 10.1016/j.spc.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Designing waste management systems to meet circular economy goals: The Italian case

Abstract: Waste management capacity plays a prominent role in complying with circular economy goals, such as reducing municipal waste disposal by landfilling to 10%. We first analyze the imbalance in municipal solid waste management across Italy by estimating the quantities of waste to be treated using technologies different from those currently in use. Subsequently, we estimate the impact that a system compliant with circular economy goals would have on the cost of waste management. Our empirical analyses are based on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Regarding the relationship with the regulatory framework, there is no clear relationship between the governance model and the cost of treatment, although consistent with previous literature, efficient costs seem to correlate with regions relying on the market for price regulation [22].…”
Section: Introductionsupporting
confidence: 78%
“…Regarding the relationship with the regulatory framework, there is no clear relationship between the governance model and the cost of treatment, although consistent with previous literature, efficient costs seem to correlate with regions relying on the market for price regulation [22].…”
Section: Introductionsupporting
confidence: 78%
“…The concept of waste is the central idea in various definitions of circular economy, according to Kirchherr et al ( 2017 ) waste is the 6th most cited term among the definitions of CRE. Researchers have illustrated that the current momentum for CRE is to take actions for better management of waste globally, in this regard, Fletcher et al ( 2021 ) and Di Foggia and Beccarello ( 2021 ) have indicated that WTM system can become sustainable through adoption of innovative technologies which help in achieving zero waste. Similarly, Kurniawan et al ( 2022 ) have also elaborated that effective implementation of TI is a driving force in moving towards zero carbon strategies in CRE framework.…”
Section: An Overview On Wtm and Ti In Cre Contextmentioning
confidence: 99%
“…The governance of the waste management industry must reach a challenging equilibrium among balancing technical efficiency through the most suitable forms of competition policies and economic regulation, economic efficiency through market forms to guarantee the production of the service at the lowest cost for the community, and universality of the service for citizens and a fair and nondiscriminatory level playing field for the companies operating in this industry (Di Foggia & Beccarello, 2021). The importance of effective governance has emerged following the European circular economy legislation that has prompted a new phase in waste management, especially regarding targets on recycling and disposal options (European Commission, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving the waste management system to ensure homogeneous accessibility, usability and dissemination throughout the country as well as adequate quality levels, there is also the objective of waste treatment infrastructure adaptation to circular economy targets (Di Foggia & Beccarello, 2021).…”
Section: Introductionmentioning
confidence: 99%